A Frequency Function and Singular Set Bounds for Branched Minimal Immersions. Issue 7 (1st May 2016) - Simon, Leon; Wickramasekera, Neshan
Abstract: We establish a frequency function monotonicity formula for two‐valued C 1, α solutions to the minimal surface system on n ‐dimensional domains. We also establish the sharp regularity result that such solutions are of class C 1, 1/2, and that their branch sets, if nonempty, have Hausdorff dimension equal to n ‐2.© 2016 Wiley Periodicals, Inc.